Differential diagnosis and management of Insomnia - S.J. Meyer (South African Family Practice)
Insomnia is the most common sleep-related complaint, and the second most common overall complaint (after pain) reported in primary care settings. It affects 35% of the general population during the course of a year but, despite its high prevalence, 69% of patients suffering from sleep disorders never report it to healthcare providers. The advent of the newer nonbenzodiazepine hypnotics has also led to an increased awareness of insomnia, and its treatment alternatives.